Single Cell Omics: From Assay Design to Biomedical Application. Issue 1 (21st October 2019) - Chen, Wenyi; Li, Shumin; Kulkarni, Anuja Shreeram; Huang, Lin; Cao, Jing; Qian, Kun; Wan, Jingjing
Abstract: Given the existence of cell heterogeneity, single cell analysis is undergoing a rapid expansion for life science and precision medicine. Recent numerous innovations in analytical platforms and instruments have re‐energized the field and led to the emergence of single cell omics with high sensitivity, throughput and multiplexity. The omics knowledge builds the bridge between underlying molecular changes and cell behavior, and facilitates a deeper understanding of disease development processes. Here, the authors highlight important achievements of single cell omics mainly including genomics, epigenomics, transcriptomics, proteomics, and metabolomics, and discuss the biomedical applications of single cell omics in stem cells differentiation, immune cells function, nerve cells development and activity, and circulating tumor cells based cancer research. Abstract : Schematic illustration of the assay designs and biomedical application of single cell omics.